2015
DOI: 10.1016/j.commatsci.2015.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of long range order of Na ions in NaxCoO2 at high temperatures by sodium site doping

Abstract: a b s t r a c tWe have systematically investigated the Na x CoO 2 system doped with Cu, Y, Sn, W, Au and Bi for x = 0.5, 0.75 and 1.00 using density functional theory. Sn, W and Bi always substitute a Co while Au always substitute a Na regardless of Na concentration. However, for, Cu and Y, the substitution site depends on Na concentration. When compared to the available experimental data, we find that thermoelectric performance is enhanced when the dopants substitute a Na site. In this case, surprisingly, res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
1
9
0
1
Order By: Relevance
“…these dopants reside in different lattice sites depending on the O partial pressure during the synthesis. The insight obtained here complements our previous work that demonstrated that the location of dopants such as Cu and Au also depends on the Na content of Na 1−x CoO 2 [34]. One of the main conclusions that we draw in this work is that the location of cationic dopants in Na 1−x CoO 2 needs to be investigated critically and the simplistic assumption based on matching ionic radii in determining dopant location can be misleading at times.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…these dopants reside in different lattice sites depending on the O partial pressure during the synthesis. The insight obtained here complements our previous work that demonstrated that the location of dopants such as Cu and Au also depends on the Na content of Na 1−x CoO 2 [34]. One of the main conclusions that we draw in this work is that the location of cationic dopants in Na 1−x CoO 2 needs to be investigated critically and the simplistic assumption based on matching ionic radii in determining dopant location can be misleading at times.…”
Section: Introductionsupporting
confidence: 78%
“…Furthermore, we can approximate the conductivity as a function of Co 4+ concentration by assuming that the carrier mobility remains 1.0 cm 2 V −1 s −1 for doped Na 1−x CoO 2 [52] for which full details are provided in table S4. This approximation is somehow conservative as dopants in Na layer are generally expected to improve carrier mobility slightly [34]. This approximation gives a conductivity value of 1.03 × 10 3 Ω −1 cm −1 for Na 0.75 CoO 2 and 2.06 × 10 3 Ω −1 cm −1 for Na 0.50 CoO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…尽管如此, 从另一 方面看, 该限制也为提升正极材料性能提供了指导方 向: 在充放电循环过程中增大 Na + 的可逆利用对电池性 能的改善将非常有利. 目前已有研究通过元素掺杂/取 代的策略来提升 Na + 的可逆利用率, 提高钠离子电池性 能 [44][45][46][47] . 2018 年 Mun 等 [48] 设计了 P2-Na 0.67 Co 与锂离子电池中常见的层状 LiCoO 2 [49][50][51] 相比(如图 3b 所示), Na x CoO 2 在充放电曲线上表现出了多个电压平 台, 表明随着 Na + 的嵌入和脱出, Na x CoO 2 经历了非常复 杂的相变过程 [52] , 可能是层内 Na + /空位复杂的有序情 况所导致的 [53] .…”
Section: 钴酸钠的电化学性能研究unclassified
“…Computational screening has recently emerged as a novel tool in the discovery of brand-new thermoelectric materials. Subsequently, through computational survey into uncharted materials’ territory, one may find a desirable oxide alternative to the common thermoelectric materials, at least for those applications where exposure to elements is inevitable. More specifically, our study was motivated by the recent prediction and observation of spinel oxides with high Seebeck coefficient and high-performance thermoelectric cubic oxides .…”
Section: Introductionmentioning
confidence: 99%